Increased lipolysis in adipose tissue and lipid mobilization to natriuretic peptides during low-calorie diet in obese women - Sengenes C; Štich, Vladimír; Berlan, M; Hejnová, Jindra; Lafontan, M; Pariskova, Z; Galitzky, J (International journal of obesity, 2002)
OBJECTIVE: We recently demonstrated that natriuretic peptides (NP) are involved in a pathway inducing lipolysis in human adipose tissue. Atrial NP (ANP) and brain NP (BNP) operate via a cGMP-dependent pathway which does not involve phosphodiesterase-3B inhibition or cAMP. The study was performed to evaluate the effect of ANP on lipid mobilization in obese women and secondly to examine the possible effect of a low-calorie diet (LCD) on the lipolytic response of subcutaneous abdominal fat cells to NP and on the lipid mobilization induced by ANP infusion (1 microg/m(2) min for 60 min). SUBJECTS: Ten obese women from 40.5+/-3.4 y old were selected for this study. Their body weight was 96.4+/-5.7 kg and their BMI was 35.3+/-1.7 kg/m(2). They received a 2.5-2.9 MJ/day formula diet for 28 days. DESIGN: Before and during the LCD, an adipose tissue biospy was performed for in vitro studies and, moreover, ANP was perfused i.v. to evaluate its lipid mobilizing action in toto and in situ in subcutaneous abdominal adipose tissue (SCAAT) using microdialysis. RESULTS: The lipolytic effects of isoproterenol, ANP, BNP and bromo-cGMP (an analogue of cGMP) on fat cells increased by about 80-100% during LCD. The lipid mobilization during i.v. ANP infusion, assessed by plasma non-esterified fatty acids (NEFA) increase was enhanced during the LCD. However, during LCD, ANP infusion induced a biphasic effect on glycerol concentration in plasma and interstitial fluid of SCAAT; a significant increase was observed in glycerol levels during the first 30 min infusion period, followed by a steady decrease. The concentration of glycerol was lower during the post-infusion period than during the baseline period. This effect was stronger in obese subjects submitted to the LCD with a low-carbohydrate composition. Other plasma parameters were weakly increased (noradrenaline) or not modified (insulin, glucose) by ANP infusion and no difference was found before and during LCD treatment. CONCLUSION: The present study shows that NP are powerful lipolytic agents in subcutaneous fat cells and that both isoproterenol- and NP-induced lipolysis increase during LCD, in obese women. These changes seem to be associated with an improvement of the lipolytic pathway at a post-receptor level. Moreover, i.v. administration of ANP induced a lipid mobilizing effect which was enhanced by a LCD in these objects.
Keywords: Female; Infusions, Intravenous; Lipid Metabolism; Diet, Reducing; Lipolysis; Isoproterenol; isoprenalin; Adipocytes; Humans; Natriuretic Agents; Adipose Tissue; Obesity; Women's Health; Natriuretic Peptide, Brain; Middle Aged; Cyclic GMP; lidé; Adult